2020
DOI: 10.1002/fsn3.1537
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in microbial survival on food contact surfaces by a spray coated polymerized quaternary ammonium compound

Abstract: Using polymerization and immobilization techniques, the loss of antimicrobial efficacy of a quaternary ammonium compound (QAC) was minimized by decreasing its solubility and crosslinking it to metal substrates. The survivability of Listeria innocua and Escherichia coli K12 inoculated to silane QAC coated metal surfaces was compared with uncoated metal surfaces at different treatment conditions for up to 6 months storage. Resilience of the coating material to repeated cleaning, up to 20 washing and rinsing cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…QAC-based coatings are known to have good antibacterial activity towards Gram-positive bacteria and enveloped viruses [14,24]. From the view of disinfection, they are bactericidal for a wide range of pathogens such as E. coli, Staphylococcus aureus, Streptococcus mutans, Bacillus subtilis, Pseudomonas aeruginosa and the fungal pathogen Candida albicans [25][26][27][28].…”
Section: Measurement Of Antibacterial Activity and Kineticsmentioning
confidence: 99%
“…QAC-based coatings are known to have good antibacterial activity towards Gram-positive bacteria and enveloped viruses [14,24]. From the view of disinfection, they are bactericidal for a wide range of pathogens such as E. coli, Staphylococcus aureus, Streptococcus mutans, Bacillus subtilis, Pseudomonas aeruginosa and the fungal pathogen Candida albicans [25][26][27][28].…”
Section: Measurement Of Antibacterial Activity and Kineticsmentioning
confidence: 99%
“…Interestingly, as Gharibi et al demonstrated, quaternary ammonium compounds can be derived from soybean oil to create biobased, nonleaching antimicrobial coatings, offering a greener synthesis approach to traditional petroleum-based antimicrobial coatings . Compared to other chemicals, quaternary ammonium compounds can be easily dissolved and do not readily evaporate and, if used within guidelines established by the Environmental Protection Agency (EPA), are considered safe . Although their antimicrobial efficacy may be reduced by the presence of organic matter (e.g., addition of 3 g/L BSA resulted in a 10-fold increase of the minimum bactericidal concentration against P. fluorescens ), their performance across a wide range of pH values still makes them desirable for food manufacturing environments, which regularly are exposed to pH extremes. , In one report, Lee and Pascall coated stainless steel with a quaternary ammonium compound derivatized silane and tested against Listeria innocua and Escherichia coli.…”
Section: Antimicrobial Agents and Mechanismsmentioning
confidence: 99%
“…Although their antimicrobial efficacy may be reduced by the presence of organic matter (e.g., addition of 3 g/L BSA resulted in a 10-fold increase of the minimum bactericidal concentration against P. fluorescens ), their performance across a wide range of pH values still makes them desirable for food manufacturing environments, which regularly are exposed to pH extremes. , In one report, Lee and Pascall coated stainless steel with a quaternary ammonium compound derivatized silane and tested against Listeria innocua and Escherichia coli. Here, the coating (compared to bare stainless steel) demonstrated superior antimicrobial efficacy (>5-log reduction for Listeria innocua , and 3–4-log reduction for Escherichia coli), but more importantly, the antimicrobial efficacy remained intact following a 20-cycle washing process . Additionally, the ability for quaternary ammonium compounds to be immobilized, via polymerization, for example, minimizes environmental release and subsequent resistance development in environmental microorganisms .…”
Section: Antimicrobial Agents and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations